Environmental Marine Geoscience 4. Continental Shelf Sediment Transport Studies in Canada: Principal Scientific Advances and Future Directions - Li, Michael; Heffler, Dave (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2002)
Summary This article, the second of two companion papers, reviews the principal scientific advances in shelf sediment transport studies in Canada, and projects future research directions. Development of new sensors and boundary layer models has led to significant improvement in our under-standing of wave-current dynamics and sediment transport processes on continental shelves. Bed shear stress and bottom roughness are found to be strongly enhanced by the interaction between waves and currents. Explicit sediment transport thresholds and ripple predictors for combined waves and currents have been proposed and partly tested. Sandre suspension strongly depends on the development of bedforms. Multibeam mapping, in combination with coring and seismic/sidescan data, has significantly improved our knowledge of the morphology and stability of sand ridges on outer-shelf sand banks. Sediment transportmodels have been significantly upgraded and calibrated based on advances incombined-flow bottom boundary layer dynamics and new in situ measurements of sediment transport. The improved models have been applied to predictregional sediment transport patterns on several Canadian continental shelves. Based on this and other reviews, future research priorities have also been identified.